Benign Convulsions with Mild Rotavirus and Norovirus Gastroenteritis: Nationwide Data from the Health Insurance Review and Assessment Service in South Korea - Kim, Dong Hyun (Children (Basel), 2021)
There have been no large-scale studies on the epidemiology of benign convulsions with mild gastroenteritis (CwG) since the introduction of the rotavirus vaccine in South Korea in 2007. This study aimed to analyze the trends in rotavirus gastroenteritis (RVGE) and rotavirus-associated CwG (RaCwG) after rotavirus vaccination. Further, we aimed to analyze changes in norovirus gastroenteritis (NVGE) and norovirus-associated CwG (NaCwG) using nationwide data from the Korean Health Insurance Review and Assessment Service. Between 2007 and 2019, this study analyzed children aged <6 years who were diagnosed with RVGE, NVGE, RaCwG and NaCwG. The changes in the prevalence of each disease and the ratio of CwG to enteritis were analyzed and the effects of age, sex and season were also analyzed. RVGE, RaCwG, NVGE and NaCwG were diagnosed in 273,898, 4246, 35,593 and 337 patients, respectively. The prevalence of RVGE was on a decreasing trend every year, but the prevalence of NaCwG and NVGE was on an increasing trend. There was a significant annual increase in the ratio of CwG to enteritis in both viruses. In order to control the prevalence of RaCwG, measures other than the rotavirus vaccine are required and measures to prevent norovirus are necessary.